Ukraine: Experience of War - Ishchuk, Natalia (Occasional papers on religion in Eastern Europe, 2022)
"The May issue of OPREE is being published during the heroic resistance of the Ukrainian people to the massive invasion of Putin’s Russian army. The unjust war of aggression launched by Russia in 2014 has been going on for more than eight years. But three months ago, the destructive leader of our neighboring state to the east wished a great victory over Ukraine. This prompted a major slaughter between the two nations."